INFORMATION ON APPLICATIONS OF TRADITIONAL MEDICINE NUTRITIOUS CONCOCTION USING MICROSOFT VISUAL BASIC 6.0 - Ambar Ari Astuti; Yudi Irawan Chandra, SKom, MMSI Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2006)
This writing describes the Application Information on Traditional Medicine nutritiousconcoction that aims to find out about the symptoms, causes, prevention, andtraditional herbs to cope with the disease. For that the author wanted to show them incomputerized form using Microsoft Visual Basic 6.0. By presenting it in the form ofcomputerization, the authors hope that the information that a typo, missing, orinappropriate can be repaired or renewed in a manner and time more efficiently. Alsoexpected this application enriches its users.